Upaya Meningkatkan Motivasi Belajar Peserta Didik Melalui Metode Hypnolearning di SMPN 1 WERU - Wulandari, Sri; Susilawati, Susilawati; Oktaviani, Tiara D.; Hidayati, Suci; Amri, Suri C.; Afeni, Tri; Pratama, Tasya P.; Rosyanti, Iis (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
The problem with this service is the low motivation of students to learn, as indicated by the fact that student attendance has not been maximised and many students are late to school. This article presents the results of a study investigating the impact of the Hypnolearning method on students' learning motivation at SMPN 1 Weru. The explanatory survey method was used in this research, with 90 respondents. Data analysis showed that students' learning motivation was in the medium category. This demonstrates the effectiveness of the Hypnolearning method in generating motivation and enthusiasm for learning.